Writing and power in the Roman world: literacies and material culture - Eckardt, Hella (Cambridge University Press, 2018)
"In this book, Hella Eckardt offers new insights into literacy in the Roman world by examining the tools that enabled writing, such as inkwells, styli and tablets. Literacy was an important skill in the ancient world and power could be and often was, exercised through texts. Eckardt explores how writing equipment shaped practices such as posture and handwriting and her careful analysis of burial data shows considerable numbers of women and children interred with writing equipment, notably inkwells, in an effort to display status as well as age and gender. The volume offers a comprehensive review of recent approaches to literacy during Roman antiquity and adds a distinctive material turn to our understanding of this crucial skill and the embodied practices of its use. At the heart of this study lies the nature of the relationship between the material culture of writing and socio-cultural identities in the Roman period"--